Optimalisasi Manajemen Persediaan Bahan Baku Pada Usaha Pabrik Mie Sinar Mandiri Kabupaten Tana Toraja - Elpasira Nirma; Marinus Ronal; Marchelin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted to find out and analyze how raw material inventory management at the Sinar Mandiri Noodle Factory Business uses the Minimum-Maxsimum method. The method used in this research is a quantitative descriptive method. The results of this research show that using the Min-Max method is more optimal than the method applied by the Sinar Mandiri Noodle Factory Business. By using the Min-Max method, you can save raw material inventory costs in 2023 amounting to IDR 6.687.111..-. Based on these results, the Sinar Mandiri Noodle Factory Business should use the Min-Max method so that raw material inventory management can be more optimal and inventory costs can be minimized so that company profits can be maximized.